Seasonality of Consumption of Nonstaple Nutritious Foods among Young Children from Nepal's 3 Agroecological Zones. Issue 9 (29th June 2018) - Broaddus-Shea, Elena T; Thorne-Lyman, Andrew L; Manohar, Swetha; Nonyane, Bareng A S; Winch, Peter J; West, Keith P
Abstract: Background: Children's dietary patterns vary seasonally, particularly in subsistence agriculture settings like Nepal, but the seasonality of nutritious nonstaple food consumption is not well explored in the literature. Objective: This study aimed to examine seasonal differences in children's consumption of provitamin A–rich fruit and vegetables, dairy, eggs, meat, and fish in Nepal's 3 agroecological zones, and to assess whether seasonal patterns vary by wealth and caste/ethnicity. Methods: Multivariable negative binomial regression models were used to analyze dietary data from 7-d food-frequency questionnaires, producing coefficient estimates in the form of incidence rate ratios (IRRs). Data were collected 3 times per year for 2 y from children aged 6–72 mo in Nepal's mountains ( n  = 226), hills ( n  = 168), and plains ( n  = 225). Results: There were significant seasonal differences in children's consumption of provitamin A–rich fruit and vegetables, dairy, meat, and fish that varied by agroecological zone. Adopting monsoon season as the referent for all comparisons, children in the mountains ate provitamin A–rich fruit and vegetables less frequently during the postmonsoon and winter seasons (IRRs: 0.5 and 0.7, respectively; both P  < 0.004), whereas in the plains, children's consumption of these foods was lower only during the postmonsoon season (IRR: 0.2; P  < 0.001). Children's dairy intake frequency increased during the winter in the mountains (IRR: 0.7; P  < 0.004) and decreased during the winter in the hills (IRR: 1.5; P  < 0.001). Only in the plains did children's meat and fish intakes vary seasonally, increasing during the postmonsoon season (IRR: 1.6; P  < 0.004). Wealth and caste/ethnicity variability influenced children's consumption of each of these nutritious groups of foods, and moderated seasonal effects in some instances. Conclusions: Children's diets varied differently by season within each agroecological zone of Nepal and in some cases across socioeconomic groups, revealing the importance of taking a season- and location-specific approach to assessing diets and tailoring dietary strategies.